Collection and Curation of Transcriptional Regulatory Interactions in Aspergillus nidulans and Neurospora crassa Reveal Structural and Evolutionary Features of the Regulatory Networks - Hu, Yibo; Qin, Yuqi; Liu, Guodong (Frontiers in Microbiology, 2018)
Transcriptional regulation has important roles in various biological processes (e.g. development and metabolism) in filamentous fungi. However, regulatory interactions between transcription factors and their target genes in these species have only been described in different forms by primary scientific literature, which limits the integrated analysis of these data. Here, we extensively curated the reported transcriptional regulatory interactions in Aspergillus nidulans and Neurospora crassa. For each interaction, the identifiers of involved proteins or genes were unified, and the types of supporting experiments were recorded. Then, transcriptional regulatory networks were reconstructed from the interactions supported by classical low-throughput experiments. Analysis of the networks revealed the presence of hub targets regulated by multiple transcription factors and network motifs of other structures (e.g. regulatory loops). Comparison of the regulatory interactions between the two species identified 33 conserved interactions supported by classical experiments in both species, most of which are involved in the regulation of metabolic genes. We anticipate the curated data would serve as a catalog for the studies of transcriptional regulation in filamentous fungi.